1970
DOI: 10.3126/mjsbh.v9i1.3484
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of Dermatological Diseases in the Patients of Army Hospital, Kathmandu

Abstract: Introduction: Human Skin is the largest organ of the body and may mirror the presence of benign/malignant systemic diseases in different ways. The pattern of Skin diseases vary in different parts ofNepal due to differences in socioeconomic and geographic factors. This retrospective study, pattern ofskin disease in Army Hospital likely reflects the pattern of disease in the Kathmandu Valley.Aim: To study, assess and compare the different patterns of skin disease in the patients attending theoutpatient departmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…Although papulosquamous disease was seen in 4.5% of total cases, psoriasis was the commonest (3.4%). In the papulosquamous group the incidence of psoriasis was highest as stated by other hospital based study from Nepal [ 19 ]. The percentage of acne in present was found to be higher compared to a hospital based study where acne vulgaris contributed to 4.1% of cases; this difference could be due to difference in diagnostic technique.…”
Section: Discussionmentioning
confidence: 64%
“…Although papulosquamous disease was seen in 4.5% of total cases, psoriasis was the commonest (3.4%). In the papulosquamous group the incidence of psoriasis was highest as stated by other hospital based study from Nepal [ 19 ]. The percentage of acne in present was found to be higher compared to a hospital based study where acne vulgaris contributed to 4.1% of cases; this difference could be due to difference in diagnostic technique.…”
Section: Discussionmentioning
confidence: 64%
“…All these studies vary in the methodology and outcome with resultant varia on in prevalence of skin diseases. Most of the studies are hospital based and few of them are community based [2][3][4][5] . The study on pa ern of skin diseases in Himalayan district of Nepal has not been documented.…”
Section: Introductionmentioning
confidence: 99%
“…Eczema (18.47%) was the most common reason to visit the OPD as was in several other studies conducted recently 8,10,14 . Eczema was the fourth common cause of OPD visit twenty years back 9 (Table 3) and second common reason ten years ago 11 in two Kathmandu based studies. Exposure to numerous chemicals, foods and cosmetics may have contributed this rise in last 20 years.…”
Section: Discussionmentioning
confidence: 99%
“…A similar study in a rurally located medical college found 3.4% of OPD visits due to urticaria. 7 However, two studies conducted one decade back have not mentioned about the urticaria in their studies, 6,11 signifying the trend of increasing urticaria is recent. Two rural community based studies found urticaria prevalence 1.8% 5 and 2.5%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation